THE IMPACT OF THE 2026 INCLUSIVE FISCAL POLICY ON ECONOMIC GROWTH IN DISADVANTAGED REGIONS: A STUDY OF DEVELOPMENT ECONOMICS THEORY AND THE IMPLEMENTATION OF PMK 105/2025 IN INDONESIA - Wulandari; Hadenan Towpek (ADISAM Publisher, 2026)
The 2026 inclusive fiscal policy through PMK 105/2025 on Government-Bearing Income Tax (DTP) has proven effective in driving economic growth in underdeveloped regions in Indonesia with a consumption multiplier effect of 1.6–1.8x among 15 million workers in labour-intensive sectors (textiles, furniture, tourism). A review of development economics theory confirms alignment with the Solow convergence model, Romer’s endogenous growth model, and Hirschman’s ‘big push’ theory to break the Myrdal circular cumulative causation in 128 priority districts. Implementation in Q1 2026 recorded a +4.8% increase in the Gross Regional Domestic Product (GRDP) of underdeveloped regions, a +22% rise in employment, and a 1.8 percentage point reduction in poverty, despite being hampered by regional fiscal capacity (85% dependence on General Allocation Funds) and governance-related leakages. Recommendations include an extension to 2027 with digitalised claims, performance-based transfers, and integration of DID-DTP to achieve 25% regional convergence within 5 years towards the 2025–2029 National Medium-Term Development Plan (RPJMN).